2005
DOI: 10.1542/peds.2004-1825
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Demographic Factors Associated With Urinary Tract Infection in Young Febrile Infants

Abstract: Being uncircumcised and height of fever were associated with UTI in febrile infants who were < or =60 days of age. Uncircumcised male infants were at particularly high risk and may warrant a different approach to screening and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
137
2
10

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(154 citation statements)
references
References 28 publications
5
137
2
10
Order By: Relevance
“…[10][11][12] Race was dichotomized into white versus nonwhite and insurance status was categorized into private versus nonprivate because of sample size limitations. Private insurance included those with health maintenance organization and preferred provider organization coverage.…”
Section: Measurementsmentioning
confidence: 99%
“…[10][11][12] Race was dichotomized into white versus nonwhite and insurance status was categorized into private versus nonprivate because of sample size limitations. Private insurance included those with health maintenance organization and preferred provider organization coverage.…”
Section: Measurementsmentioning
confidence: 99%
“…Pyonephritis is seen in 34-70% of those with febrile UTI, (62) where UTI is the cause of the fever in 21% of uncircumcised boys, 2% of circumcised boys and 5% of girls. (63) An imaging study found that 50-86% of children admitted with febrile UTI and presumed pyelonephritis had renal parenchymal defects. (64) These persist, and a 27-year follow-up study found elevated risk of hypertension and endstage renal disease in 10%, (65) meaning ongoing morbidity and costs from an infant UTI.…”
Section: Penile Cancermentioning
confidence: 99%
“…Изолированная пиурия, бактериурия или положи-тельный нитратный тест у детей до 6 мес не являются достоверными признаками инфекции мочевыводящих путей [20][21][22][23][24][25][26].…”
Section: диагностика инфекции мочевыводящих путейunclassified